2021
DOI: 10.1002/nop2.758
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining acceptance of disease and its impact on satisfaction with life of patients with peripheral artery disease

Abstract: Atherosclerosis is the most common cause of peripheral artery disease (PAD) (Zdrojowy et al., 2010), which requires long-term treatment. Clinical manifestations of PAD include intermittent claudication, rest pain and tissue necrosis (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…A third of patients with vascular diseases (34%) showed a low disease acceptance rate, significantly higher than those in patients treated surgically for other diseases in this study (14%) and a study by other authors (16.4%) (Lelonek & Kaczmarczyk, 2011). The results presented in this study in terms of mean values obtained for the entire AIS in patients with vascular diseases (25.90) are comparable to those of other authors in the group of patients with PAD (25.17) (Piotrkowska et al, 2021) and slightly lower than in the group of patients after operation of varicose veins of lower limbs (27.00) (Wiśniewska-Szumacher et al,…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A third of patients with vascular diseases (34%) showed a low disease acceptance rate, significantly higher than those in patients treated surgically for other diseases in this study (14%) and a study by other authors (16.4%) (Lelonek & Kaczmarczyk, 2011). The results presented in this study in terms of mean values obtained for the entire AIS in patients with vascular diseases (25.90) are comparable to those of other authors in the group of patients with PAD (25.17) (Piotrkowska et al, 2021) and slightly lower than in the group of patients after operation of varicose veins of lower limbs (27.00) (Wiśniewska-Szumacher et al,…”
Section: Discussionsupporting
confidence: 86%
“…Adapting to the disease is an understanding of the actual health condition, which allows the patient to cope with the problems of the disease, including the sensation of pain (Bono et al, 2013;Dance, DeBerard, Gundy Cuneo 2016). Studies have confirmed that people who accept the disease show greater trust in doctors, treatment methods, a positive hopeful approach to life and active participation in therapy (Boryczko-Pater et al, 2011;Piotrkowska et al, 2021). The disease acceptance is an important element in the process of adapting to living with the disease, especially one with a troublesome tendency to relapse as well as situations related to a certain perception of the disease by society.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have been conducted in the field of accepting the disease and its impact on the satisfaction of patients with chronic diseases, health outcomes and their quality of life [20,[54][55][56][57][58]. Siregar and Rhamayani (2019) conducted a study with the aim of examining self-acceptance of chronic caused failure in patients who have a hemodialysis in Medan.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Chiu et al(2021) and Goodman et al (2021) who examined the effect of educational programs on patient satisfaction concluded that the experimental group more satisfied with the educational program delivered. Additionally, Piotrkowska et al(2021) revealed that continued health teaching increased patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%